Effectiveness of E-Poster-Based Umbilical Cord Care Education on Primiparous Postpartum Mothers’ Knowledge of Neonatal Infection Prevention - Sulastri Sulastri; Linda Tri Ani (Jurnal Ners, 2026)
Umbilical cord infection (omphalitis) remains one of the causes of neonatal infection in Indonesia, with a prevalence of approximately 5–10%, while in Lampung Province it reaches 6.3%. Lack of knowledge among primiparous mothers regarding umbilical cord care is a risk factor for infection, therefore effective education using e-poster media is needed. This study aimed to determine the effectiveness of e-poster education on umbilical cord care toward knowledge of infection prevention among primiparous postpartum mothers at RSUD Jendral Ahmad Yani Kota Metro. This study used a pre-experimental design with a one group pre-test post-test approach. The sample consisted of 25 respondents selected using purposive sampling technique. The research instruments included e-posters, educational SOPs, and knowledge questionnaires. Data were analyzed using paired sample t-test. The results showed that before the intervention, most respondents had poor knowledge, accounting for 15 respondents (60.0%), while after the intervention, most respondents had good knowledge, accounting for 17 respondents (68.0%). The paired sample t-test showed a p-value of 0.000 (<0.05) with a mean difference of 7.72, indicating that e-poster education was effective in improving knowledge of umbilical cord infection prevention among primiparous postpartum mothers. In conclusion, e-poster education is effective in increasing the knowledge of primiparous postpartum mothers regarding umbilical cord infection prevention.